Weasels, minks and fishers—orphan rehabilitation of the slinky carnivores, Part 2: care protocols for orphaned infants and Juveniles - Popp, Peggy (Wildlife Rehabilitation Bulletin, 2025)
<p style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Mustelids are highly specialized, efficient predators with special care needs while in a rehabilitation setting. The following intake and orphan care protocols for select North American mustelids is a combination of natural history, literature review, established orphaned wildlife rehabilitation procedures, professional consultations and personal experience. The protocols address some of the unique characteristics and requirements of these slinky carnivores, while also providing tools necessary for successful rehabilitation and release. Part 1: Natural History (Popp 2024) discusses the natural history of North American weasels, minks and fishers, including physical characteristics, habitat and diet, and how these factors may be used to inform their intake and care protocols when brought into the rehabilitation setting. Part 2: Care Protocols for Orphaned Infants and Juveniles discusses vetted care protocols for orphaned weasels, minks and fishers based on their natural history and established orphaned wildlife rehabilitation procedures. Part 3: Pre-Release Conditioning and Release discusses the steps involved in preparing these species for a successful release.